Students' reflective writing through journal on blogs: A case study of part 3 students of UiTM Johor / Zuraidah Sumery - Sumery, Zuraidah (2014)
Reflection involves the evaluation of feelings, ideas and opinions of past and current experiences for future references. Reflection redefines our understanding of knowledge and makes us aware of our actions and enables us to evaluate our actions. Reflection, either reflected-on-action or reflected-in-action can be documented through the use of reflective writing. Four types of reflective writing are "Descriptive writing", "Descriptive Reflection", "Dialogic Reflection" and "Critical Reflection". This study examined students' reflective writing via the usage of free Internet BlogSpot blog by exploring students' experiences in English for Academic Writing purpose (BEL 311) classes. A purposive sampling method was used to select 30 part three students of Faculty of Business Management at UiTM Johor. Three research questions were examined: (1) What are the most common types of reflective writing do the students tend to employ indirectly in their reflections?; (2) How far do the students use reflection-in-action and reflection-on-action in their reflections?; (3) How do students view their reflections in learning writing skills? For this study, data from 395 reflections were analyzed using a constant comparative analysis. The findings reported that the students' reflections were mostly Reflection-On-Action (88%) as compared to Reflection-In-Action (12%). The findings also recorded the occurrences of different types of reflective writing which were "Descriptive Reflection" (48%), "Descriptive writing" (43%), "Dialogic Reflection" (7%) and "Critical Reflection" (2%). Some reflections indicated a combination of two or more types of reflective writing. Students reflected more on-action because they did not have sufficient knowledge and skills that enabled them to solve any encountered problems immediately. In their blog writing, the students applied various types of reflective writing that included their feelings, opinions, perceptions and learning experiences. All these new experiences of web-based reflective writing using blogs can lead to important implications for effective instruction and learning strategies.